A kinetic study on mercury oxidation by HCl over typical Mn-based SCR catalysts. (1st December 2022) - Zhang, Shibo; Zhang, Qingzhu; Díaz-Somoano, Mercedes; Dang, Juan; Xu, Yang; Zhao, Yongchun; Zhang, Junying
Graphical abstract: Highlights: Hg 0 oxidation over the Mn-based catalysts followed L-H mechanism proven by kinetics. The reaction rate constants showed an advantage over some other catalysts. The kinetic parameters were further improved with the addition of O2 into flue gas. The apparent activation energy was much lower than that of the other approaches. Abstract: A kinetic approach was adopted to analyze the reaction mechanism of elemental mercury (Hg 0 ) oxidation by HCl over three Mn-based low-temperature SCR catalysts, MnOx /TiO2, Fe-MnOx /TiO2 and CeMnO3 . Experimental results validated that Hg 0 oxidation efficiencies of the catalysts were promoted by HCl at different temperatures. The kinetic models for the heterogeneous Hg 0 oxidation were established and verified based on the experimental data. The verification results demonstrated that Hg 0 oxidation over the Mn-based catalysts follows Langmuir-Hinshelwood mechanism. The kinetic parameters of reaction rate constant and HCl adsorption constant were calculated from the model fitting equations. The reaction rate constant was raised with the increase of temperature, while the HCl adsorption constant presented the opposite trend. The Mn-based catalysts with the reaction rate constant of 84.17–335.77 s −1 showed the advantage over some other catalysts such as commercial V2 O5 -(WO3 )/TiO2 and CeO2 /TiO2 . The kinetic parameters were further improved in the presence of O2 . The apparent activation energy for Hg 0 oxidation over the catalysts that was derived from the kinetic parameters was 4.13–12.53 kJ/mol, which was much lower than that of the other approaches. The advantageous kinetic parameters and apparent activation energy were favorable for the Mn-based catalysts to act as low-temperature SCR catalyst for synergistic Hg 0 removal. The kinetic study results were of fundamental significance for designing the reactor according to the known flue gas conditions, used catalyst and required Hg 0 oxidation efficiency.